(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Cultural architectural vocabularies are not only rich but diverse and they usually reflect their unique cultural expressions. These vocabularies cut across all building components, such as; roof structures, walling and flooring systems, finishes, materials, and a host of others. This study documents local architectural vocabularies for residential building components in Nigeria cultures with focus on Yoruba residential buildings in Oyo State. Using qualitative research approach, traditional building components of Yoruba residential buildings were identified, and their features documented. The cultural and historical significance were analysed. The building layout, room divisions, structural systems, roof forms, wall treatments, and decorative motifs were identified as the key Yoruba architectural elements. Thirty-five (35) building components were identified and the pictorial and yoruba language interpretations were documented in a tabular form “See table 3.1”. The alignment of buildings with the cardinal points reflects the spiritual significance and connection with the natural world. The decorative motifs used in Oyo architecture hold symbolic meanings. The "adinkra" motif represents the interconnectedness of all things in the universe. Modernization, urbanization, and socio-economic changes pose threats to the continuity of traditional building practices. The increasing use of modern building materials and standardized construction methods diminishes the authenticity and uniqueness of Oyo architecture. The documentation of thesevocabularies is essential for the preservation and promotion of cultural heritage,as well as for the development of sustainable building practices that are rooted in local traditions. The findings of theresearch highlight the cultural significance and symbolism embedded within the architectural vocabularies of the Oyo tribe.